Effects of auditory feedback on fine motor output and corticomuscular coherence during a unilateral finger pinch task - Guo, Jing; Liu, Tian; Wang, Jue (Frontiers in Neuroscience, 2022)
Auditory feedback is important to reduce movement error and improve motor performance during a precise motor task. Accurate motion guided by auditory feedback may rely on the neural muscle transmission pathway between the sensorimotor area and the effective muscle. However, it remains unclear how neural activities and sensorimotor loop play a role in enhancing performance. The present study uses an auditory feedback system by simultaneously recording electroencephalogram, electromyography and exert force information to measure corticomuscular coherence, neural activity and motor performance during precise unilateral right-hand pinch by using the thumb and the index finger with and without auditory feedback. This study confirms three results. Firstly, compared with no auditory feedback, auditory feedback decreases movement error. Secondly, compared with no auditory feedback, auditory feedback decreased the power spectrum in the beta band in the bimanual sensorimotor cortex and the alpha band in the ipsilateral sensorimotor cortex. Finally, corticomuscular coherence was computed between effector muscle of right hand and contralateral sensorimotor cortex. Analyses reveals that the corticomuscular coherence of beta band significantly decreases in auditory feedback condition compared with no auditory feedback condition. The results indicate that auditory feedback decreases the power spectral in the alpha and beta band and decreases corticospinal connection in the beta band during precise hand control. This study provides a new perspective on the effect of auditory feedback on behavior and brain activity, offers a new idea on designing more suitable and effective rehabilitation and training strategies to improve fine motor performance.